Preparation and characterization of fired bricks made from bottom ash and iron slime - Mandal A.K.; Sinha O.P. (My University, 2025)
This paper presents experimentally investigated results of iron slime addition as additives in making bottom ash bricks. Bottom ash from coal burning thermal power stations of two different fineness (i.e., 1-0.2 mm and 0.075-0 mm) are mixed with varying contents of iron slime. Green bricks were dried and subsequently fired for 2 h at 1,000, 1,100, and 1,200°C. The strength and density of fired bricks increased with increasing firing temperature, fineness of bottom ash, and iron slime content, but decrease in porosity. With increasing firing temperature, the formation of iron silicate followed by iron aluminum silicate occurs, which is mainly responsible for imparting the strength of the bricks. The amount of lower melting phases increases with increasing iron slime content even at lower firing temperature, which is also responsible for increasing the strength and bulk density but reducing the porosity after subsequent cooling. The results suggest iron slime can be used as a binding material for making bottom ash bricks, even when fired at a lower temperature. © 2016 American Society of Civil Engineers.